THE EVOLUTION OF THE CONCEPTIONS OF THE SOCIALLY RESPONSIBLE BUSINESS'S DEVELOPMENT - Evgenia Zagaynova (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with a number of the stages of socially responsible business's development in accordance with the changing tendency in business. I stage «The negation of social responsibility for business», it's characterized by profit maximization, efficiency of labour's improvement. II stage «Corporate social responsibility::. The improvement of the staff's quality of life; the formation and development of the local society is typical for this stage. III stage «The prospective social responsibility}}. Discussing this stage one can mark out: environment protection, orientation on the institution of interaction